Multi-camera framing of dry slope snowboarding jumps - Decorte, R.; De Waele, R.; Slembrouck, M.; Verstockt, S. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: While snowboarding was originally only performed in mountainous regions, the popularity of this sport combined with the unpredictability of natural snowfall has led to the creation of dry slopes, i.e., man-made artificial surfaces that simulate the feel of snow, allowing for year-round snowboarding practice and training. To enhance the experience at the dry slope, we've developed an automated video system that provides detailed jump analysis. Using three cameras, we capture athletes from multiple angles and generate zoomed-in videos for review. Our analysis reports, distilled from these videos, includes key metrics like airtime, takeoff speed, height, and distance.